Impact of gestational weight gain on obstetric and neonatal outcomes in obese diabetic women. Issue 1 (December 2015) - Gante, Inês; Amaral, Njila; Dores, Jorge; Almeida, Maria
Abstract Background Both obesity and gestational diabetes mellitus are increasing in prevalence, being a major health problem in pregnancy with independent and additive impact on obstetrics outcomes. It is recognized that inadequate gestational weight gain is an independent risk factor for pregnancy-related morbidity. The aim of this study was to evaluate the effect of gestational weight gain on obstetric and neonatal outcomes in obese women with gestational diabetes. Methods Retrospective multicenter study of obese women with gestational diabetes. The assessed group was divided into three categories: women who gained below (<5 kg), within (5–9 kg) and above (>9 kg) the 2009 Institute of Medicine recommendations. Maternal and neonatal outcomes were compared and adjusted odds ratios calculated controlling for confounders. Results Only 35, 1 % of obese women with gestational diabetes (n  = 634) achieved the recommended gestational weight gain; 27, 8 % (n  = 502) gained below and 37, 1 % (n  = 670) above the recommendations. There was a positive correlation between gestational weight gain and neonatal birthweight (r  = 0, 225;p  < 0, 001). Gestational weight gain below recommendations was associated with lower odds for cesarean section, even adjusting for birthweight [aOR = 0, 67 (0, 54–0, 85);p  < 0, 001]; lower odds for large for gestational age neonates [aOR = 0, 39 (0, 28–0, 57);p  < 0, 001] and macrosomia [aOR = 0, 34 (0, 21–0, 55);p  < 0, 001]. Excessive weight gain, even adjusting for birthweight, was associated with higher odds for cesarean section [aOR = 1, 31 (1, 07–1, 61);p  = 0, 009], low Apgar score [aOR = 4, 79 (1, 19–19, 21);p  = 0, 027], large for gestational age neonates [aOR = 2, 32 (1, 76–3, 04);p  < 0, 001] and macrosomia [aOR = 2, 39 (1, 68–3, 38);p  < 0, 001]. Conclusions In obese women with gestational diabetes, a reduced gestational weight gain (<5 kg) is associated with better obstetric and neonatal outcomes than an excessive or even an adequate weight gain. Therefore, specific recommendations should be created since gestational weight gain could be a modifiable risk factor for adverse obstetric outcomes.